Quality Preservation and Shelf-Life Extension of Prickly Pear (Opuntia ficus-indica L. Mill) Using Edible Coatings - Carolina Rodrigues; Cariny Polesca; Isabela Bicalho; Victor Gomes Lauriano Souza; Isabel Coelhoso; Ana Luísa Fernando (Foods)
Prickly pear consumption is increasing across the world due to its rich variety of nutrients and bioactive compounds. Yet, it is a seasonal and highly perishable fruit, and the application of edible coatings emerges as an alternative to extend its shelf life. In this work, the effects of alginate, starch, chitosan, and pectin as coatings on the physicochemical, bioactive, microbiological, and textural properties of two prickly pear varieties (orange and red), kept under refrigeration (5 ± 2 °C) were evaluated for 6 weeks. Coatings proved to be helpful in the maintenance of the fruits’ color and textural properties, especially when pectin was applied. Overall, starch and chitosan can be considered the most effective coatings in preserving the quality of prickly pears among the options studied. A lower weight loss (8–10%) in fruits was achieved when starch and chitosan were applied, while in control fruits (without coating), the loss was 18–23%. Starch and chitosan also contributed to preserving the bioactivity of red fruits and showed good results in the preservation of total phenolic content in the orange fruits. In addition, starch and chitosan coatings also presented the best performance for the reduction of microbial contamination (both yeasts and molds and total mesophilic aerobic microorganisms). These findings highlight the role of edible coatings in preserving prickly pears, for a longer period, meeting consumers’ demand for fresh fruit.